RESTRAINING TURNOVER RATE: THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT IN EMPLOYEE DUAL ROLE CONFLICT(A STUDY OF EMPLOYEES AT PT TERMINAL PETIKEMAS, SURABAYA) - Wita Fauziah; Sri Astuti Pratminingsih (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to examine the effect of Work-Family Conflict on Turnover Intention with Organizational Commitment as a mediating variable among employees of PT Terminal Petikemas Surabaya. The research approach used is quantitative with an explanatory type, using survey methods and path analysis. The sample consisted of 80 permanent employees who are married, with the criteria of minimum work experience of one year. The results of the study indicate that Work-Family Conflict has a significant negative effect on Organizational Commitment, and a significant positive effect on Turnover Intention. Conversely, Organizational Commitment has a negative effect on Turnover Intention. The mediation test using the Sobel Test shows that Organizational Commitment significantly mediates the effect of Work-Family Conflict on Turnover Intention. Employees who experience role conflict pressure tend to have high turnover intentions, but this can be suppressed by a strong organizational commitment. These findings confirm that strengthening Organizational Commitment is a key strategy in managing the dynamics of role conflict and maintaining workforce stability and retention in the organization.